The van der Waals CdO/PtS2heterostructures for photocatalytic water splitting with excellent carrier separation and light absorption - Ahmad, Iqtidar; Shahid, Ismail; Ali, Anwar; Zeb, Shakeel [UNESP]; Gao, Lei; Cai, Jinming (Royal Society of Chemistry (RSC), 2021)
The creation of hydrogen by photocatalytic water splitting is a core research area in the worldwide attempts to discover a valid substitute for fossil fuels. Here, van der Waals CdO/PtS2 heterostructures for photocatalytic water splitting with excellent carrier separation and light absorption are reported based on first-principles calculations. Heterostructures with different stacking arrangements, CdO/PtS2-A and CdO/PtS2-B, possess suitable band edges for photocatalytic water splitting. The type-II band alignment with an intrinsic electric field produces efficient resistance to photo-induced charge carrier recombination. The charge carriers are more highly competent to reach the surface and participate in the reaction, which subsequently improves the photocatalytic performance due to a much smaller effective mass of electrons and holes. Moreover, the heterostructures exhibit enhanced optical absorption with an enormous absorption coefficient (105 cm-1) for absorption over a wide range of the visible spectrum compared to monolayers, which represents an efficient boost in photocatalytic activity. Our results demonstrate that CdO/PtS2 is an auspicious and exceptional photocatalyst for solar water splitting. This journal is